Succinate dehydrogenase inhibition with malonate during reperfusion reduces infarct size by preventing mitochondrial permeability transition. (23rd December 2015) - Valls-Lacalle, Laura; Barba, Ignasi; Miró-Casas, Elisabet; Alburquerque-Béjar, Juan José; Ruiz-Meana, Marisol; Fuertes-Agudo, Marina; Rodríguez-Sinovas, Antonio; García-Dorado, David
Abstract: Aims: Previous studies demonstrated that pre-treatment with malonate, a reversible inhibitor of succinate dehydrogenase, given before ischaemia, reduces infarct size. However, it is unknown whether administration of malonate may reduce reperfusion injury. Methods and results: Isolated mice hearts were treated, under normoxic conditions, with increasing concentrations of disodium malonate (0.03–30 mmol/L, n = 4). Malonate induced a concentration-dependent decrease in left ventricular developed pressure (LVdevP) (EC50 = 8.05 ± 2.11 mmol/L). In isolated hearts submitted to global ischaemia (35 min) followed by reperfusion (60 min), malonate 3 mmol/L given only during the first 15 min of reperfusion reduced lactate dehydrogenase release (125.41 ± 16.82 vs. 189.20 ± 13.74 U/g dry tissue/15 min in controls, P = 0.015) and infarct size (24.57 ± 2.32 vs. 39.84 ± 2.78%, P = 0.001, n = 7–8 per group) and improved recovery of LVdevP (20.06 ± 3.82 vs 7.76 ± 2.53% of baseline LVdevP, P = 0.017). 1 H NMR spectroscopy demonstrated marked changes in the metabolic profile of malonate-treated hearts, including increased accumulation of succinate. Furthermore, malonate reduced reactive oxygen species (ROS) production, as measured by MitoSOX staining in myocardial samples obtained after 5 min of reperfusion and in mitochondrial preparations from these samples, preserved mitochondrial respiration, and reduced mitochondrial permeabilization, assessed by calcein retention. Treatment with malonate did not result in activation of RISK or SAFE signalling pathways in tissue extracts obtained 5 min after reperfusion. Conclusion: Succinate dehydrogenase inhibition with malonate at the onset of reperfusion reduces infarct size in isolated mice hearts through reduction in ROS production and mitochondrial permeability transition pore opening.